Periodontal disease and quality of life: Umbrella review of systematic reviews - Wong, Li Beng; Yap, Adrian Ujin; Allen, Patrick Finbarr (Journal of periodontal research, 2021)
This umbrella review appraised existing systematic reviews and meta‐analysis to establish the impact of periodontal disease and therapy on general and oral health‐related quality of life. A systematic electronic literature search was carried out in accordance with the PRISMA guideline up to January 2020 using PubMed, LIVIVO, EMBASE and OpenGrey (PROSPERO CRD 42020163831). Hand searching was performed through the reference lists of periodontal textbooks and related journals. All English language‐based systematic reviews and meta‐analysis that assessed the impact of periodontal disease and treatment interventions on general and oral health‐related quality of life were included. Overall, eight articles met the inclusion criteria and their methodological quality was assessed using the AMSTAR2 criteria. Two systematic reviews showed a significant impact of oral conditions on general health‐related quality of life, although the specific impact of periodontal disease remains inconclusive. Three systematic reviews established a negative impact of periodontal disease on oral health‐related quality of life. Another three systematic reviews concluded that periodontal treatment can improve oral health‐related quality of life. Oral conditions, like periodontal disease, can impact the general health‐related quality of life. Periodontal disease is negatively correlated with oral health‐related quality of life, although treatment interventions can improve self‐reported quality of life. In view of the heterogeneity of generic instruments currently utilized to assess the self‐reported quality of life of periodontal patients, the development of a general and oral health‐related quality of life instrument specific for periodontal disease is strongly recommended.